2012
DOI: 10.1016/j.soard.2012.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathology before surgery in the Longitudinal Assessment of Bariatric Surgery-3 (LABS-3) Psychosocial Study

Abstract: Background Current and prior psychopathology in bariatric surgery candidates is believed to be common. Accurate prevalence estimates, however, are difficult to obtain given that bariatric surgery candidates often wish to appear psychiatrically healthy when they are undergoing psychiatric evaluation prior to being approved for the surgery. Also, structured diagnostic assessments have been utilized infrequently. Methods This report concerns the 199 patients who were enrolled in the Longitudinal Assessment of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
168
1
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 243 publications
(192 citation statements)
references
References 45 publications
14
168
1
9
Order By: Relevance
“…Usually greater in women (Carpenter et al, 2000;de Wit et al, 2010;Heo et al, 2006;Mitchell et al, 2012), depressive symptoms that develop in obese individuals often present atypical features such as increased appetite/weight gain, mood reactivity, and hypersomnia/fatigue (Chou and Yu, 2013;Levitan et al, 2012;Lojko et al, 2015). In agreement with this, overweight, obesity, and metabolic abnormalities, including leptin deregulation, appear to be more prevalent in atypical depression than in melancholic/typical depression (Chou and Yu, 2013;Cizza et al, 2012;Lamers et al, 2010;Lasserre et al, 2014;Levitan et al, 2012;Milaneschi et al, 2015).…”
Section: Fat and Depression: A Vicious Circlementioning
confidence: 95%
“…Usually greater in women (Carpenter et al, 2000;de Wit et al, 2010;Heo et al, 2006;Mitchell et al, 2012), depressive symptoms that develop in obese individuals often present atypical features such as increased appetite/weight gain, mood reactivity, and hypersomnia/fatigue (Chou and Yu, 2013;Levitan et al, 2012;Lojko et al, 2015). In agreement with this, overweight, obesity, and metabolic abnormalities, including leptin deregulation, appear to be more prevalent in atypical depression than in melancholic/typical depression (Chou and Yu, 2013;Cizza et al, 2012;Lamers et al, 2010;Lasserre et al, 2014;Levitan et al, 2012;Milaneschi et al, 2015).…”
Section: Fat and Depression: A Vicious Circlementioning
confidence: 95%
“…Interviews were conducted independently of the routine pre-surgery screening process. Methods and baseline data on psychiatric disorders have been reported previously (5). Of note, the SCID screener for alcohol use disorder required reporting having drunk five or more drinks on one occasion, a threshold that might be too high after bariatric surgery given evidence that alcohol pharmacokinetics may be altered by some procedures, thereby decreasing tolerance (20)(21)(22)(23).…”
Section: Methodsmentioning
confidence: 99%
“…Studies employing structured clinical interviews have revealed high lifetime rates of mood disorders (range: 22.0 -54.8%) and anxiety disorders (range: 15.5 -37.5%) prior to surgery. Most also suggest high lifetime rates for alcohol abuse and dependence, but documented rates vary widely (range: 0.7 -33.2%) (3)(4)(5)(6)(7). Although bariatric surgery is the most effective treatment for severe obesity (8,9), post-surgery weight loss is highly variable, even among patients undergoing the same procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Al respecto, el abuso o dependencia activa de sustancias ha sido considerado como una de tan solo cuatro contraindicaciones claras para cirugía bariátrica de acuerdo a guías y consensos internacionales, recomendando además una evaluación psicológica rutinaria a los candidatos 5 . Aunque numerosos reportes han mencionado la alta probabilidad de psicopatología en pacientes en espera de resolución quirúrgica, los resultados tienden a ser dispares y son pocos los que han utilizado entrevistas estructuradas 6 . Trabajos recientes han sugerido que tener una historia previa de trastornos relacionados al consumo de sustancias es más frecuente en aquellos que consultan por cirugía bariátrica en comparación al resto de la población 7,8 .…”
Section: Discussionunclassified